2020
DOI: 10.3390/foods9040428
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Consumer Liking for Beef, Pork, and Lamb: A Review

Abstract: Tenderness, juiciness, and flavor have been associated with consumer acceptance of beef, lamb, and pork. Drivers of consumer liking are interrelated across these species, but there are differences in consumer preferences. Animal age, animal diet, and subsequent marbling impact consumer liking across species. For beef, consumer research prior to the 1990s showed that tenderness was the main driver of liking. Consumer tenderness and juiciness liking are highly correlated. More recent research has shown that as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 189 publications
1
70
2
6
Order By: Relevance
“…However, more recent studies have shown that as overall tenderness improved and tenderness variation decreased, flavor has become a more important driver of beef consumer liking. In general, as long as tenderness and juiciness are at acceptable levels, flavor is the main driver of overall liking [27,28]. In the present study, beef from steers and heifers scored higher for flavor (4.86 in both cases) than beef from bulls.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 39%
“…However, more recent studies have shown that as overall tenderness improved and tenderness variation decreased, flavor has become a more important driver of beef consumer liking. In general, as long as tenderness and juiciness are at acceptable levels, flavor is the main driver of overall liking [27,28]. In the present study, beef from steers and heifers scored higher for flavor (4.86 in both cases) than beef from bulls.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 39%
“…Trained assessors typically perform objective sensory analysis and, therefore, remain the most appropriate tool to perceive and explain possible differences among treatments [ 38 ]. Consumers, however, even if they are not trained to discriminate among different food-related sensory attributes, represent the final market goal, i.e., every food product is produced to meet consumers’ demands and acceptance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, meat is regarded as one of the main sources of animal protein [ 4 , 5 ] and lamb is known to be highly nutritious and digestible [ 6 ], fortified with essential amino acids, iron, zinc, selenium, fatty acids and vitamins A, B6 and B12 [ 5 ]. Lamb also has relatively low lipid and saturated fat contents compared to meat from other ruminants [ 7 ], and its marbling, tenderness, juiciness, aroma and colour attributes have been known to influence consumer liking [ 8 ], carcass [ 9 ], meat assignment into quality grades [ 10 ], consumer food choices [ 11 ] and nutritional value [ 12 ]. It is therefore very important that sheepmeat producers guarantee the consistency of their lamb products in order to meet consumer preferences and adapt to the dynamics of purchasing decisions based on meat eating quality.…”
Section: Introductionmentioning
confidence: 99%